Comparison of the Minimental State Examination Scale and the International HIV Dementia Scale in Assessing Cognitive Function in Nigerian HIV Patients on Antiretroviral Therapy - O. Olajumoke Oshinaike; A. Akinsegun Akinbami; O. Oluwadamilola Ojo; I. Frank Ojini; U. Njideka Okubadejo; A. Mustapha Danesi (AIDS Research and Treatment)
Introduction. HIV-associated neurocognitive disorder (HAND) remains common despite the availability of antiretroviral therapy. Routine screening will improve early detections. Objective. To compare the performance of the minimental state examination (MMSE) and international HIV dementia scale (IHDS) in assessing neurocognitive function in HIV/AIDS patients on antiretroviral therapy. Methods. A case-control study of 208 HIV-positive and 121 HIV-negative individuals. Baseline demographic data were documented and cognitive function assessed using the two instruments. CD4 cell counts were recorded. Results. Cases comprised 137 females and 71 males. Controls were 86 females and 35 males. Mean MMSE score of cases was 27.7±1.8 compared to 27.8±1.3 in controls (P=0.54). Mean IHDS score in cases was 8.36±3.1 compared to 10.7±0.9 in controls (P<0.001). Using the MMSE scale, 6 cases but no controls had HAND (P=0.09). Using the IHDS, 113 (54.3%) had HAND compared with 10 (8.3%) controls (P<0.0001). Using IHDS, 56.5% cases with CD4 count > 200 had HAND compared with 92.5% with CD4 count < 200 (P<0.001). Conclusion. These findings indicate that the IHDS detects higher rates of HAND and may identify HIV/AIDS patients who require further cognitive assessment using more robust assessment batteries.